Effect of a Virtual Platform on Undergraduate Students’ Achievements in Horticultural Crop Production in Northern Nigeria - Saulawa, Bishir Umar; Abdulhamid, Auwal; Shuaibu, Babawuro; Hassan, Sanusi; Garba, Abubakar Sadiq (International Journal of Computing Sciences Research, 2023)
Purpose – This study intends to test a virtual platform for teaching undergraduate students horticultural crop production in Northern Nigeria. Method – This research work engaged a quasi-experimental design to test a virtual platform on horticultural crop production achievement among undergraduate students in northern Nigeria. The design was commonly used in this situation because a randomized assignment is not possible in practice, especially in the sampled universities where lecture rooms cannot be re-organised to accommodate the experimentation procedure. Results – The results revealed that undergraduate students exposed to virtual platforms perform better than those exposed to conventional approaches, a significant difference exists between the mean performance of undergraduate students exposed to the virtual platform and those exposed to conventional approaches. Conclusion – The application of a virtual platform as substituting approach in teaching horticultural crop production proved to be effective means of improving students’ academic performance. In the course of treatment, the experimental group of undergraduate students proved more attentive to the teaching process because the budding, layering and grafting were explained through interactive activities of animations, which contributed significantly to student learning. Recommendations – It was recommended that the universities management should provide enabling virtual environment and facilities where suitable video and animations should be used to teach undergraduate students and special training should be organized for agricultural science teachers/lecturers on the use of a virtual platform. Research Implications – The use of virtual instruction has provided replies to encourage the incorporation and adaptation of virtual platform environments in higher institutions of learning as an alternative to conventional approaches to teaching. In addition, virtual classroom instruction and the online education experience in higher institutions of learning are beneficial to undergraduate students' achievement.